Design of an "allsolid-state'' supercapacitor based on phosphoric acid doped polybenzimidazole (PBI) electrolyte - Rathod, Dhanraj; Vijay, Meenu; Islam, Md. Nazrul; Kannan, Ramaiyan; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan (Journal of Applied Electrochemistry, 2009)
The effectiveness of phosphoric acid doped polybenzimidazole as a polymer electrolyte membrane to fabricate an all solid-state super capacitor has been explored using hydrous RuO(2)/carbon composite electrodes (20 wt.%) of surface area 250 m(2) g(-1) with many intrinsic advantages. The electrochemical evaluation of these super capacitors through cyclic voltammetry, charge/discharge and impedance measurements demonstrate the utility of this type of thin, compact and flexible supercapacitor capable of functioning at 150 degrees C to yield a maximum capacitance of about 290 F g(-1) along with a life of more than 1,000 cycles. A power density of 300 W kg(-1) and energy density of 10 Wh kg(-1) have been accomplished although the equivalent series resistance (ESR) of about 3.7 Omega needs to be reduced further for high rated applications.
Keywords: Electrochemical characterization; Electrochemical supercapacitor; Energy storage device; PBI electrolyte; RuO(2)/carbon composite